ANALISIS STILISTIKA DAN NILAI PENDIDIKAN KARAKTER PADA IKLAN RADIO GITANADA FM KECAMATAN DIWEK KABUPATEN JOMBANG - Fajarudin Fiyantoni; Wawan Hermawan; Doni Uji Windiatmoko (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2018)
This study aims to describe the characteristics of diction, style and image related to character education. The formal object of this study is the stylism associated with diction, language style and image with character education. And the material object is an advertisement on Gitanada FM Tebuireng Jombang radio that contains many diction characteristics, language styles and images related to character education. The data obtained from the radio number of 17 data in the form of recording and the author of the transcript itself. The technique used in this research is using observation and recording or record technique. The method used is descriptive qualitative method that produces descriptive data in the form of words written or spoken from the people and behavior that can be observed. Of the 17 data, researchers have classified the types of ads into eight of them, property ads, service ads, vehicle ads, clothing and accessories advertising, educational advertising, drug advertising, beverage advertising and public advertising. From the classification of the ads obtained data for diction 31, including common word there are seven data, special word there are seven data, abstract word there are five data, concrete word there are four data, seven for popular word and three for scientific word. There are 13 data for the grouping of language styles from six kinds of language styles which the author finds, one person's data style, two data hyperbola, four data repetition, one data metonemia, three data aliases and two lithotes. And Nine data for images, including visual imagery, touch-up image, tasting image and motion imagery. For the value of character education writer got five data in the form of peace love there is one data, friendly data one, care about the environment one data, social care data one, honesty there is one data. Keywords: Stylistic Analysis, Character Education